ANALISIS KESTABILAN LERENG MENGGUNAKAN METODE JANBU PADA LERENG PERMUKAAAN LUBANG BMK-14 DI CV. BARA MITRA KECANA DI DESA BATU TANJUNG, KECAMATAN TALAWI, KOTA SAWAHLUNTO, PROVINSI SUMATERA BARAT - Wahyu Dicky Guntara; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
CV. Bara Mitra Kencana is a company engaged in mining and has invested in the city of Sawahlunto. The mineral that has been mined is coal. Administratively, the location of the Exploitation KP is in Tanah Kuning, Batu Tanjung Village, Talawi District, Sawahlunto City, West Sumatra Province with an area of 70.53 hectares. The results of the study were landslides that occurred in the CV area. Bara Mitra Kencana-14 is a planar sliding with a landslide rate of 85% in the direction of the N87oE/44o landslide. Therefore a recommendation for a single slope with a height of 35 m and an initial slope of 80o is changed to a slope of 64o and the safety factor (FK) in the natural state is 1.403 and the safety factor (FK) in saturated conditions is 1.260 and the factor of safety (FK) in the natural state is 1.403. safety (FK) in dry conditions is 1.509 and the slope is said to be in relatively safe conditions.